Antibacterial performance of nickel-doped ZIF-67-driven heterojunction enhanced stent and preparation method of nickel-doped ZIF-67-driven heterojunction enhanced stent

By doping Ni2+ in ZIF-67 and carbonizing treatment, and preparing a composite biological scaffold combined with PCL, the problem of biofilms hindering the antibacterial effect was solved, and efficient chemical dynamics, photodynamics, and photothermal synergistic antibacterial effects were achieved.

CN119454947APending Publication Date: 2025-02-18JIANGXI UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411524987.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

When the polycaprolactone (PCL) biostent is directly introduced into the zeolite imidazole salt framework-67 (ZIF-67), its antibacterial effect is limited due to the presence of biofilms.

Method used

By doping the conductive metal ion Ni2+ in ZIF-67 and carbonizing it, a Ni@ZIF-C functional carbon material was obtained. Combining Ni@ZIF-C with PCL, selective laser additive manufacturing technology was used to prepare a composite biostent with high specific surface area and controllable nanostructure.

Benefits of technology

It improves the antibacterial performance and photothermal stability of the biological scaffold, and can continuously generate reactive oxygen species under near-infrared light irradiation, effectively destroying the biofilm and enhancing oxidative damage to bacteria, achieving the synergistic antibacterial effect of chemical dynamics, photodynamics, and photothermal.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119454947A_ABST
    Figure CN119454947A_ABST
Patent Text Reader

Abstract

The invention discloses antibacterial performance of a nickel-doped ZIF-67 driven heterojunction enhanced scaffold and a preparation method of the nickel-doped ZIF-67 driven heterojunction enhanced scaffold, and the preparation method comprises the following steps: synthesizing Ni (at) ZIF through a coprecipitation reaction, and performing high-temperature carbonization to obtain Ni (at) ZIF-C powder; ni-coated ZIF-C and PCL are dispersed in ethyl alcohol, and PCL / Ni-coated ZIF-C composite powder is obtained through stirring, centrifuging, drying and the like; the PCL / Ni-coated ZIF-C biological scaffold is manufactured through an additive manufacturing technology, the problem that when a PCL scaffold is directly introduced into ZIF-67, the antibacterial performance of the biological scaffold can be reduced due to the existence of a biological membrane is solved, due to the fact that the atomic radius of Ni < 2 + > ions is similar to that of Co < 2 + > ions, Co < 2 + > can be partially replaced to change the crystallinity and the energy band structure, and therefore the generation efficiency of photoelectrons and ROS is improved; a functional carbon material with a high specific surface area and a controllable nanostructure can be obtained through carbonization treatment on ZIF-67, light can be converted into heat under near infrared (NIR) laser irradiation, more ROS is induced to enter bacteria, oxidative damage to the bacteria is generated, and therefore the purpose of chemical power, photopower and photo-thermal synergistic antibacterial is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of biological scaffold preparation, and in particular to a nickel-doped ZIF-67 driven heterojunction enhanced scaffold with antibacterial performance and a preparation method thereof. Background Art

[0002] Bacterial infection has long been considered a major challenge to wound healing. Even drug-resistant bacteria have emerged, which plague patients and often lead to long-term wound healing. The complexity of bacterial infection is reflected in its multi-stage process, including bacterial adhesion, biofilm formation, host invasion and transmission. Zeolitic imidazolate framework-67 (ZIF-67) has acid degradation specificity and peroxidase-like (POD) activity, which can convert hydrogen peroxide (H2O2) into highly toxic hydroxyl radicals (·OH), causing oxidative damage to bacteria. Polycaprolactone (PCL) is one of the few biomedical materials approved by the US Food and Drug Administration (FDA). It has good processability, biocompatibility and degradability. It is enzymatically decomposed into carbon dioxide and water in the human body and excreted from the body through urine. The combination of the two can effectively combat bacterial infection of skin implants, but due to the presence of biofilm, its antibacterial effect is limited to a certain extent.

[0003] Doping of conductive metal ions Ni in ZIF-67 2+ It is expected to improve its photocatalytic activity due to Ni 2+ The atomic radius of the ion and Co 2+ Ions are similar and can partially replace Co 2+ The crystallinity and band structure are changed, thereby improving the generation efficiency of photoelectrons and ROS. Importantly, by carbonizing ZIF-67, functional carbon materials with high specific surface area and controllable nanostructure can be obtained, which can convert light into heat under near-infrared (NIR) laser irradiation while improving its catalytic performance.

[0004] The introduction of near-infrared light can not only improve the catalytic activity of Ni@ZIF-C, but more importantly, it can damage the biofilm, allowing more ROS to enter the bacteria and cause oxidative damage to the bacteria, thereby achieving the purpose of chemical power, photodynamic power, photothermal synergistic antibacterial and even anti-biofilm.

[0005] There is currently no report on the use of Ni@ZIF-C / PCL bioscaffolds that combine chemical power, photodynamic power, and photothermal synergy to combat skin infections. Summary of the invention

[0006] In order to solve the problem that biofilm hinders the antibacterial effect when polycaprolactone (PCL) biological scaffold is directly introduced into zeolite imidazolate framework-67 (ZIF-67), the present invention provides a nickel-doped ZIF-67 driven heterojunction enhanced scaffold with antibacterial performance and a preparation method thereof.

[0007] To achieve the above object, the present invention provides the following technical solution: a nickel-doped ZIF-67 driven heterojunction enhanced antibacterial performance of the scaffold and a preparation method thereof, comprising the following steps:

[0008] S1, obtaining Ni@ZIF by coprecipitation method, and then carbonizing the obtained Ni@ZIF at high temperature to obtain Ni@ZIF-C powder;

[0009] S2, dispersing PCL powder in anhydrous ethanol to obtain PCL suspension, and then dispersing Ni@ZIF-C powder in the PCL suspension to obtain P·CL / Ni@ZIF-C mixed suspension, and then subjecting to ultrasonication, magnetic stirring, centrifugation, drying, grinding and other steps to obtain PCL / Ni@ZIF-C composite powder;

[0010] S3. PCL / Ni@ZIF-C composite powder was used to manufacture PCL / Ni@ZIF-C bioscaffold through selective laser additive manufacturing technology.

[0011] Preferably, in step S1, the Ni@ZIF powder is synthesized to obtain the Ni@ZIF-C powder, and the steps are as follows:

[0012] S11. Add Co(NO3)2·6H2O and Ni(NO3)2·6H2O to 120 mL of methanol, named solution A, and add 2-methylimidazole to 40 mL of methanol, named solution B;

[0013] S12, slowly pouring solution A into solution B, stirring at room temperature until it turns into a blue-purple liquid, incubating at room temperature for 24 hours, collecting the resulting purple precipitate by centrifugation, repeatedly washing with ethanol, and drying in a vacuum oven to obtain Ni@ZIF powder;

[0014] S13. Carbonize the obtained Ni@ZIF powder in a N2 environment for 2 h to obtain Ni@ZIF-C powder.

[0015] Preferably, in step S11, the amounts of Co(NO3)2·6H2O and Ni(NO3)2·6H2O used are 8 mmol and 4 mmol respectively, and the amount of 2-methylimidazole is 48 mmol.

[0016] Preferably, in step S13, the carbonization temperature is 800°C.

[0017] Preferably, in step S11, the molar ratio of Co(NO3)2·6H2O to Ni(NO3)2·6H2O is 2:1-3:1.

[0018] Preferably, in step S2, the dispersion method used is ultrasound and magnetic stirring, the ultrasonic dispersion time is 10-60min, the temperature is 15-40°C, the magnetic stirring dispersion time is 0.5-6h, the speed is 300-800r / min, the temperature is 30-60°C, the centrifugal time is 10-60min, the centrifugal speed is 1000-5000r / min, the temperature of the vacuum drying oven is 50-80°C, the drying time is 5-24h, and the powder time after grinding and drying is 3-20min.

[0019] Preferably, in step S13, the synthesized Ni@ZIF-C is a rhombic dodecahedron, and the particle size of the synthesized Ni@ZIF-C powder is 100-1000 nm.

[0020] Preferably, in step S12, in step S2, the particle size of PCL is 0.1-5 um, and the purity is greater than 99%.

[0021] Preferably, in step S1 and step S3, in the PCL / Ni@ZIF-C bioscaffold, the weight fraction of Ni@ZIF-C is 5-30%, and the weight fraction of PCL is 70-95%.

[0022] Preferably, in step S3, the PCL / Ni@ZIF-C composite powder is placed in a 3D printing system and sintered layer by layer according to the set three-dimensional modeling. The steps of preparing the biological scaffold are: preheating the powder to a temperature slightly lower than the melting point; flattening the rod to spread the powder; sintering the powder layer by layer with a laser beam; removing the unsintered excess powder to obtain a composite biological scaffold, and the process parameters of selective laser sintering are: laser power of 0.5-4W, scanning spacing of 0.3-1.0mm, scanning speed of 50-200m / s, spot diameter of 300-1000mm, and powder bed preheating temperature of 60-80℃.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] The present invention dopes the conductive metal ion Ni in ZIF-67 2+ It is expected to improve its photocatalytic activity due to Ni 2+ The atomic radius of the ion and Co 2+ Ions are similar and can partially replace Co 2+The crystallinity and band structure are changed, thereby improving the generation efficiency of photoelectrons and ROS. Importantly, by carbonizing ZIF-67, functional carbon materials with high specific surface area and controllable nanostructure can be obtained, which can convert light into heat under near-infrared (NIR) laser irradiation while improving its catalytic performance.

[0025] The introduction of near-infrared light in the present invention can not only improve the catalytic activity of Ni@ZIF-C, but more importantly, it can damage the biofilm, so that more ROS can enter the bacteria and cause oxidative damage to the bacteria, thereby achieving the purpose of chemical power, photodynamic power, photothermal synergistic antibacterial and even anti-biofilm.

[0026] The present invention adds Ni@ZIF-C into a PCL matrix to prepare a composite bioscaffold, and Ni@ZIF-C can be used as a bridge to improve the mechanical strength of the PCL scaffold. The PCL / Ni@ZIF-C bioscaffold has good photothermal stability and can continuously generate reactive oxygen.

[0027] The present invention utilizes selective laser additive manufacturing technology to manufacture a composite biological scaffold with controllable porosity and personalized customization. Ni is substituted by ions and combined with organic ligands to make the scaffold structure more stable. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 It is a schematic diagram of the overall process of the present invention;

[0029] Figure 2 The number of bacterial colonies and the corresponding scanning electron microscope images after 6 hours of culture on different biological scaffolds in Example 1;

[0030] Figure 3 Crystal violet staining images of bacteria and different biological scaffolds after 48 hours of co-culture in Example 1;

[0031] Figure 4 These are the ROS fluorescence images inside bacteria treated with different biological scaffolds in Example 1. DETAILED DESCRIPTION

[0032] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0033] For example, please refer to Figure 1-4 The present invention provides a technical solution: a nickel-doped ZIF-67 driven heterojunction enhanced antibacterial performance of the scaffold and a preparation method thereof, comprising the following steps:

[0034] 8mmol Co(NO3)2·6H2O and 8mmol Ni(NO3)2·6H2O were added to 120mL methanol, named solution A, 48mmol 2-methylimidazole was added to 40mL methanol, named solution B, solution A was slowly poured into solution B and stirred at room temperature until it turned into a blue-purple liquid. After incubation at room temperature for 24 hours, the purple precipitate was collected by centrifugation and washed repeatedly with ethanol. The centrifugation time was 5 minutes and the centrifugal speed was 10000 / min. The solution after centrifugation was dried in a vacuum oven at 60℃ for 12 hours, and then the obtained powder was carbonized at 800℃ for 2h in a N2 environment to obtain Ni@ZIF-C powder.

[0035] 19g PCL powder was dispersed in 500mL anhydrous ethanol and ultrasonically treated for 1 hour at an ultrasonic temperature of 25°C to obtain a PCL suspension; then 1g Ni@ZIF-C powder was dispersed into the PCL suspension, the ultrasonic dispersion time was 30 minutes, the magnetic stirring dispersion time was 4 hours, and the magnetic stirring time was 25°C to obtain a uniformly dispersed PCL / Ni@ZIF-C mixed suspension; then centrifugal treatment was performed, the centrifugal time was 10 minutes, the centrifugal speed was 10000r / min, the drying time was 12 hours, and the powder time after grinding and drying was 10 minutes to obtain a Ni@ZIF-C composite powder.

[0036] The PCL / Ni@ZIF-C composite powder was placed in a 3D printing device and sintered layer by layer according to the settings of the 3D modeling software to prepare a bioscaffold. The steps for preparing the bioscaffold are as follows: preheating the powder to a temperature slightly below the melting point; flattening the rod to spread the powder; sintering the powder layer by layer with a laser beam; removing the excess unsintered powder to obtain a PCL / Ni@ZIF-C bioscaffold, recorded as 5wt% PCL / Ni@ZIF-C. The main process parameters are: laser power of 1.0W, scanning spacing of 0.4mm, scanning speed of 100m / s, spot diameter of 400mm, and powder bed preheating temperature of 60℃.

[0037] In this example, the antibacterial rate of the PCL / Ni@ZIF-C composite bioscaffold can reach more than 99%. In the antibacterial experiment, under near-infrared light irradiation, the PCL / Ni@ZIF-C composite bioscaffold has excellent antibacterial effect on bacteria.

[0038] In this example, the anti-biofilm rate of the PCL / Ni@ZIF-C composite bioscaffold can reach more than 60%.

[0039] Figure 1The number of bacterial colonies and the corresponding scanning electron microscope images after 6 hours of culture on different bioscaffolds in Example 1 indicate that the PCL / Ni@ZIF-C bioscaffold has excellent antibacterial ability under near-infrared light irradiation. Figure 2 This is the crystal violet staining image after the bacteria and different biological scaffolds were co-cultured for 48 hours in Example 1, which reflects the anti-biofilm ability of different scaffolds. It can be seen that the color of the PCL / Ni@ZIF-C+NIR group is the lightest, indicating that the ability to destroy biofilm is the strongest. Figure 3 The fluorescence images of ROS inside bacteria treated with different bioscaffolds in Example 1 show that the fluorescence intensity of the PCL / Ni@ZIF-C+NIR group is the highest, indicating that more ROS entered the bacteria in the PCL / Ni@ZIF-C+NIR group.

[0040] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A nickel-doped ZIF-67 driven heterojunction enhanced scaffold with antibacterial properties and a preparation method thereof, characterized in that: The following steps are involved: S1, obtaining Ni@ZIF by coprecipitation method, and then carbonizing the obtained Ni@ZIF at high temperature to obtain Ni@ZIF-C powder; S2, dispersing PCL powder in anhydrous ethanol to obtain PCL suspension, and then dispersing Ni@ZIF-C powder in the PCL suspension to obtain P·CL / Ni@ZIF-C mixed suspension, and then subjecting to ultrasonication, magnetic stirring, centrifugation, drying, grinding and other steps to obtain PCL / Ni@ZIF-C composite powder; S3. PCL / Ni@ZIF-C composite powder was used to manufacture PCL / Ni@ZIF-C bioscaffold through selective laser additive manufacturing technology.

2. The antibacterial performance of a nickel-doped ZIF-67 driven heterojunction enhanced scaffold and its preparation method according to claim 1, characterized in that: In step S1, Ni@ZIF powder is synthesized to obtain Ni@ZIF-C powder, and the steps are as follows: S11. Add Co(NO3)2·6H2O and Ni(NO3)2·6H2O to 120 mL of methanol, named solution A, and add 2-methylimidazole to 40 mL of methanol, named solution B; S12, slowly pouring solution A into solution B, stirring at room temperature until it turns into a blue-purple liquid, incubating at room temperature for 24 hours, collecting the resulting purple precipitate by centrifugation, repeatedly washing with ethanol, and drying in a vacuum oven to obtain Ni@ZIF powder; S13. Carbonize the obtained Ni@ZIF powder in a N2 environment for 2 h to obtain Ni@ZIF-C powder.

3. The antibacterial performance of a nickel-doped ZIF-67 driven heterojunction enhanced scaffold and its preparation method according to claim 2, characterized in that: In the step S11, the amounts of Co(NO3)2·6H2O and Ni(NO3)2·6H2O selected are 8 mmol and 4 mmol respectively, and the amount of 2-methylimidazole is 48 mmol.

4. The antibacterial performance of a nickel-doped ZIF-67 driven heterojunction enhanced scaffold and its preparation method according to claim 2, characterized in that: In the step S13, the carbonization temperature is 800°C.

5. The antibacterial performance of a nickel-doped ZIF-67 driven heterojunction enhanced scaffold and its preparation method according to claim 2, characterized in that: In the step S11, the molar ratio of Co(NO3)2·6H2O to Ni(NO3)2·6H2O is 2:1-3:

1.

6. The antibacterial performance of a nickel-doped ZIF-67 driven heterojunction enhanced scaffold and its preparation method according to claim 1, characterized in that: In the step S2, the dispersion method is ultrasound and magnetic stirring, the ultrasonic dispersion time is 10-60min, the temperature is 15-40°C, the magnetic stirring dispersion time is 0.5-6h, the speed is 300-800r / min, the temperature is 30-60°C, the centrifugal time is 10-60min, the centrifugal speed is 1000-5000r / min, the temperature of the vacuum drying oven is 50-80°C, the drying time is 5-24h, and the powder time after grinding and drying is 3-20min.

7. The antibacterial performance of a nickel-doped ZIF-67 driven heterojunction enhanced scaffold and its preparation method according to claim 2, characterized in that: In the step S13, the synthesized Ni@ZIF-C is a rhombic dodecahedron, and the particle size of the synthesized Ni@ZIF-C powder is 100-1000 nm.

8. The antibacterial performance of a nickel-doped ZIF-67 driven heterojunction enhanced scaffold and its preparation method according to claim 1, characterized in that: In the step S2, the particle size of PCL is 0.1-5 um, and the purity is greater than 99%.

9. The antibacterial performance of a nickel-doped ZIF-67 driven heterojunction enhanced scaffold and a preparation method thereof according to claim 1, characterized in that: In the step S3, in the PCL / Ni@ZIF-C bioscaffold, the weight fraction of Ni@ZIF-C is 5-30%, and the weight fraction of PCL is 70-95%.

10. The antibacterial performance of a nickel-doped ZIF-67 driven heterojunction enhanced scaffold and a preparation method thereof according to claim 1, characterized in that: In the step S3, the PCL / Ni@ZIF-C composite powder is placed in a 3D printing system and sintered layer by layer according to the set three-dimensional modeling. The steps of preparing the biological scaffold are: preheating the powder to a temperature slightly lower than the melting point; flattening the rod to spread the powder; sintering the powder layer by layer with a laser beam; removing the unsintered excess powder to obtain a composite biological scaffold. The process parameters of selective laser sintering are: laser power of 0.5-4W, scanning spacing of 0.3-1.0mm, scanning speed of 50-200m / s, spot diameter of 300-1000mm, and powder bed preheating temperature of 60-80℃.